2007
DOI: 10.1159/000103645
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Clinically Atypical with Typical Chronic Inflammatory Demyelinating Polyradiculoneuropathy

Abstract: Background: There is a paucity of prospective studies evaluating the atypical features of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). Aims: To compare clinical and electrodiagnostic features of clinically typical and atypical CIDP patients. Methods: The patients with typical and atypical CIDP diagnosed according to the European Federation of Neurological Societies/Peripheral Nerve Society were included. The disability was graded on a 0–10 scale. Neurophysiological study included motor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
2
9
0
3
Order By: Relevance
“…Two studies found a higher level of disability and impairment in patients with typical CIDP than in patients with LSS and DADS 6 30. Another study did not find a difference in terms of disability between typical and atypical CIDP 31. In our series, patients with typical CIDP had a worse MRC score, higher disability and worse QoL than patients with DADS, confirming that DADS is clinically less disabling than typical CIDP.…”
Section: Discussionsupporting
confidence: 68%
“…Two studies found a higher level of disability and impairment in patients with typical CIDP than in patients with LSS and DADS 6 30. Another study did not find a difference in terms of disability between typical and atypical CIDP 31. In our series, patients with typical CIDP had a worse MRC score, higher disability and worse QoL than patients with DADS, confirming that DADS is clinically less disabling than typical CIDP.…”
Section: Discussionsupporting
confidence: 68%
“…2 Hand dynamometer values of patients with motordominant CIDP before and after IVIg therapy 2.8 ± 1.5 years, range 1-5 years), the average number of relapses was 5.8 ± 2.2 (n = 5, range 4-9). Within the first year after the disease onset, the average number of relapses was 3.8 ± 1.1 (n = 5, range [2][3][4][5]. From the first to the second year after the disease onset, the average number of relapses decreased to 2.3 ± 1.9 (n = 4, range 1-5).…”
Section: Therapy and Prognosismentioning
confidence: 99%
“…The subtypes of CIDP differ in clinical presentation, electrophysiological and laboratory features, and response to treatment [1]. There are several reports on the cases of patients with motor-dominant CIDP who showed selective motor involvement upon clinical and electrophysiological examination [2][3][4]. Furthermore, the clinical, pathological, electrophysiological, and prognostic features of patients with motor-dominant CIDP are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…8,13 In our study, we further classified a-CIDP in to distal CIDP (d-CIDP) with distal symmetric involvement without proximal weakness 14 and multifocal CIDP (m-CIDP) with asymmetric weakness. 15,16 Distal CIDP is also referred to by some authors as distal acquired demyelinating symmetrical neuropathy without a monoclonal protein-I.…”
Section: Cidp Phenotypes-typical and Atypical Cidpmentioning
confidence: 99%